Bangunan Pasar Tradisional Petojo Enclek: Penerapan Sistem Teknologi sebagai Bukti Perbaikan Kualitas Hidup dan Perubahan Lingkungan di Batavia Abad ke-20 – 21 - Argi Arafat (KALPATARU, 2021)
Abstract. Traditional markets are places and means of meeting sellers and buyers and are marked by direct buyer-seller transactions and usually there is a bargaining process. This research is a study of environmental changes and Petojo Enclek Market in the 20th - 21st Century. The purpose of this research is to see changes in Petojo Enclek Market based on archives, ancient maps, ancient photos, history, technology used in buildings, and market conditions in the past. recently. In this study using qualitative methods, the stages of this research include data collection, data processing, data analysis and data interpretation. The theory used in this study is the Core-Periphery by John Friedman and Weaver, where the Core-Periphery relationship can occur due to the expansion (development) of markets and other infrastructure. This research, it can be seen that there are significant changes in the Petojo Enclek Market building and its surroundings.